The Host’s Politeness Strategies in Ellen Degeneres Reality Talk Show - Ruansyah, Rajif Alif; Rukmini, Dwi (English Education Journal, 2018)
Language has a significant role in communication. As social being, almost everyday people use language to communicate with others such as communication over the telephone or a direct conversation. In conversation there was a certain rule wich has to be learned to avoid misunderstanding. It was called politeness. Talk Show was television program that amuse poeple because of the conversation and joke in it. In this study the writer focused on Ellen Show inform the USAfor the following reasons. First, it was one favorite Talk Show in USA. Second, there are few people talking about politeness. Politeness can make relationship better with the other. Hence, the writer examined it in the talk show. The last, related to the data, the writer found the contribution of impoliteness used by the host to ELT.There were two data collection methods used in this research: the video of the talkshow and the transcription of the interview. Based on the analysis, the reseacher found kind of politeness strategies used by the host. There are four types of politeness strategies employed by Ellen Degeneres in the Ellen Show when having conversations with the guest star. They are bald-on record, positive politeness, negative politeness, and off-record strategy. The politeness strategies contribute to make the realitationship between people closer and make all learn how to appreciate others.